2018
DOI: 10.2196/jmir.9306
|View full text |Cite
|
Sign up to set email alerts
|

Internet and Social Media Access Among Youth Experiencing Homelessness: Mixed-Methods Study

Abstract: BackgroundYouth experiencing homelessness are at a risk for a variety of adverse outcomes. Given the widespread use of the internet and social media, these new technologies may be used to address their needs and for outreach purposes. However, little is known about how this group uses these resources.ObjectiveThis study investigated how homeless adolescents use these technologies for general and health-related purposes, whether the scope of their use changes with housing status, and their interest in a website… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“… 12 Further, technology access is consistent across the lifespan, with similar rates being found among homeless youth, adults, and older adults. 12 – 16 Persons experiencing homelessness use technology and the internet to stay connected with family and friends, search for housing and employment, and contact employers and case workers. 11 , 17 – 19 Further, persons experiencing homelessness are open and willing to use technology for health-related purposes.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Further, technology access is consistent across the lifespan, with similar rates being found among homeless youth, adults, and older adults. 12 – 16 Persons experiencing homelessness use technology and the internet to stay connected with family and friends, search for housing and employment, and contact employers and case workers. 11 , 17 – 19 Further, persons experiencing homelessness are open and willing to use technology for health-related purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of smartphones over the past decade has created an additional means by which to disseminate drug‐related information. In an assessment of Internet use among youth living in homeless shelters, 86% reported accessing the Internet at least once per week, and 66% reported accessing the Internet primarily on a smartphone (VonHoltz et al, 2018). Thus, it is plausible to anticipate that rates of smartphone and Internet use would be at least this high in our sample of youth who were either actively homeless, living with friends or family, or had an apartment or house of their own.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies among YEH have indicated that use of communication technology is ubiquitous among this population, with 80%-90% of YEH indicating using some form of communication technology; additionally, these studies indicate that technology is the main avenue through which YEH reach out to their broader networks (e.g., homebased peers, family, etc. ; Rice & Barman-Adhikari, 2014;VonHoltz et al, 2018). Together, these findings may indicate the need to rethink how we specify boundaries for designating YEH sociometric networks.…”
Section: Limitationsmentioning
confidence: 92%